Strengthening School Community Preparedness through FAST Education, Health Literacy, and Stroke Emergency Response Simulation - Siti Rohimah; Maryammah Maryammah; Acep Hidayatul Mustopa; Santo Imanuel Tonapa; Gita Cahyani Cahyani; Dani Usmar Usmar; Ade Azis; Sri Mulyani Rahman; Ningsih Nur Hidayati; Ira Zulfa Rahma; Kevin Satriady; Nurjanah Nurjanah; Bunga Mar’atun Nailla; Fadila Rahayu; Samrotul pitriyah (International Journal of Community Service (IJCS), 2026)
Stroke outcomes are strongly influenced by how quickly people recognize warning signs and activate emergency care, yet school communities are rarely prepared to respond to a suspected stroke occurring among teachers, staff, families, or visitors. This community-service program strengthened school preparedness through an integrated package of FAST education, stroke-related health literacy, guided emergency simulation, and development of a School Emergency Response System. The program was implemented at SMA Negeri 1 Ciamis, West Java, Indonesia, with teachers, student members of the School Health Unit, supervising teachers, and UKS personnel. Evaluation used an unmatched pre-post design because anonymous respondent codes were not available. The evaluation included 68 pre-activity and 14 post-activity responses, which were analyzed using Mann-Whitney U tests, Holm correction, and rank-biserial effect sizes. Post-activity scores were higher for stroke knowledge and case recognition (79.0±13.3 vs. 92.3±11.1; adjusted p=.002), health literacy (58.8±19.7 vs. 73.1±13.0; adjusted p=.012), and emergency response readiness (61.5±15.6 vs. 67.9±9.7; adjusted p=.036). The largest practical gain concerned avoiding oral food, fluids, or medication for a person with suspected stroke, while uncertainty remained about whether symptoms could be observed for 30-60 minutes. The program suggests that schools can become meaningful community nodes for stroke recognition when concise messages, reflective discussion, simulation, and institutional response procedures are combined. Continued reinforcement, paired follow-up evaluation, and routine UKS simulation are recommended.